Exploring the role of Epstein-Barr virus infection on the clinical features and survival in locally advanced cervical cancer: a retrospective cohort study - Castro-Uriol, Denisse; Vera, Juana; Valcarcel, Bryan; López-Ilasaca, Marco; Yabar, Alejandro; Cámara, Anaís; Malpica, Luis; Beltrán, Brady (Frontiers in Oncology, 2024)
IntroductionEpstein-Barr virus (EBV) infection has been linked to cervical cancer (CC), but few have described the clinical and outcome features of patients with CC and EBV infection.MethodsWe conducted a single-center matched cohort study on 94 patients with CC. Real-time Polymerase chain reaction (RT-PCR) was used to detect EBNA-1 (Epstein-Barr nuclear antigen 1) and LMP-1 (Latent membrane protein 1). We used Kaplan-Meier and Cox regression analysis to evaluate the effect of EBV infection on overall survival (OS) and progression-free survival (PFS). Females with a positive EBV status were matched to those without infection using a propensity score.ResultsOf the 94 patients in our cohort, 21 (22%) had a positive EBV status. Before and after matching, there were no differences in baseline clinical and sociodemographic features between patients diagnosed with CC with and without EBV infection. Most patients received concurrent chemoradiotherapy (73%) as frontline treatment. With a median follow-up of 67 months, the 5-year OS was 42% (95% CI: 33–55%) and the 5-year PFS was 37% (95% CI: 37–49%) in the entire population. Patients with EBV-positive status had comparable 5-year OS (50% vs. 37%, p-value=0.490; Hazard Ratio [HR] 0.77, 95% CI 0.36-1.62) and 5-year PFS (44% vs. 37%, p-value=0.750; HR 0.89, 95% CI 0.43-1.83) to those with EBV-negative CC, respectively.ConclusionFemales with CC and EBV infection have similar clinical features and outcomes compared to those without EBV infection.